2023
DOI: 10.1021/acs.jafc.3c01733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aflatoxins and Fumonisins, Alone or in Combination, on Performance, Health, and Safety of Food Products of Broiler Chickens, and Mitigation Efficacy of Bentonite and Fumonisin Esterase

Phillis Emelda Ochieng,
Siska Croubels,
David Kemboi
et al.

Abstract: The current study evaluated the effects of feeding diets contaminated with aflatoxin B1 (AFB1), fumonisins (FBs), or both on the performance and health of broiler chickens and the safety of their food products as well as the efficacy of bentonite and fumonisin esterase to mitigate the effects of these mycotoxins under conditions representative for sub-Saharan Africa (SSA). Four hundred one-day-old Cobb 500 broiler chickens were randomly assigned to 20 treatments with either a control diet, a diet with moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(175 reference statements)
1
0
1
Order By: Relevance
“…However, neither AFM1/AFM2 nor AFL could be recovered even in livers from broilers receiving AFB1 alone. In this respect, our data are in line with those of Ochieng et al (2023), who did not find AFM1/AFM2 (the only checked metabolites) in livers from broilers administered with higher doses (0.060 or 0.120 mg AFB1/kg feed) for a longer time (35 days) [51]. In partial contrast to our results, Micco et al (1988) found hepatic undetectable amounts of AFM1, along with 1200 ng/kg AFL, in broilers dietarily treated with 0.060 mg AFB1/kg for 36 days [49].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, neither AFM1/AFM2 nor AFL could be recovered even in livers from broilers receiving AFB1 alone. In this respect, our data are in line with those of Ochieng et al (2023), who did not find AFM1/AFM2 (the only checked metabolites) in livers from broilers administered with higher doses (0.060 or 0.120 mg AFB1/kg feed) for a longer time (35 days) [51]. In partial contrast to our results, Micco et al (1988) found hepatic undetectable amounts of AFM1, along with 1200 ng/kg AFL, in broilers dietarily treated with 0.060 mg AFB1/kg for 36 days [49].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the dietary inclusion of very low levels of AFB1 (0.02 mg/kg), only for a short period (10 days), resulted in measurable AFB1 liver concentrations in the 36–81 ng/kg range. Our results are difficult to compare with data from the literature since, in the few reports in which similar toxin concentrations (0.050 to 0.120 mg/kg diet) were used, the exposure duration was much longer (28 to 64 days) [ 33 , 49 , 50 , 51 ]. In such studies, AFB1 hepatic levels ranging from <LOQ (40 ng/kg) to 400 ng/kg were found.…”
Section: Discussioncontrasting
confidence: 68%